Achieving Harmony among Different Social Identities within the Self-Concept: The Consequences of Internalising a Group-Based Philosophy of Life - Turner-Zwinkels, Felicity M.; Postmes, Tom; van Zomeren, Martijn (PLOS ONE, 2015)
It can be hard for individuals to manage multiple group identities within their self-concept (e.g., being a Christian and a woman). We examine how the inter-identity fit between potentially conflicting identities can become more harmonious through a self-defining group philosophy for life. Specifically, we test the hypothesis that holistic group identities (based in group philosophies for life that prescribe the behavior of their members in any situation, such as religion) become more strongly related to other identities in the self-concept (e.g., gender) when they are strongly self-defining (i.e., devotedly applied to daily life). In three studies we investigated the inter-identity fit between individuals’ (highly holistic) religious identity and (less holistic) gender identity. Results provided converging support for our hypothesis across diverging methods (explicit questionnaires, more implicit associations, and a novel network analysis of group traits). We discuss the importance of understanding how some (i.e., holistic and self-defining) group identities may harmonize otherwise less harmonious group identities within one’s self-concept.